Cooperative cation substitution facilitated construction of garnet oxynitride MgY2Al3Si2O11N:Ce3+ for white LEDs. Issue 12 (5th June 2018) - Pan, Zaifa; Wang, Ruiping; Li, Weiqiang; Wu, Haiqin; Chen, Jiacheng; Zheng, Yifan
Abstract: Structural modification is an important means to induce redshift of Ce 3+ emission in garnet phosphor. We intend to design and synthesize garnet oxynitride compounds which combine attributes of rigidity inherited from garnet structure and of high covalence characteristic of oxynitride compounds. However, impurity phase usually occurs in the nitridation of garnet phosphor, due to the low solubility of nitrogen in oxides. We herein exploit the cooperative cation substitution strategy to facilitate the incorporation of nitrogen in Y3 Al5 O12 . It is found that partial substitution of Y 3+ ‐Altet 3+ pairs by Mg 2+ ‐Si 4+ pairs can diminish the phase instability caused by the replacement of Altet 3+ ‐O 2− by Si 4+ ‐N 3− . A novel pure garnet phase oxynitride phosphor MgY2 Al3 Si2 O11 N:Ce 3+ with a higher substitution content of N has been obtained and the successful incorporation of N in the garnet phosphor is confirmed by the Rietveld refinements of XRD, XPS, and TEM. The emission and excitation spectra indicate that the blue‐light‐excitable MgY2 Al3 Si2 O11 N:Ce 3+ phosphor exhibited a bright yellow‐orange emission peaking at 570 nm, which is redshifted by 28 nm when compared to YAG:Ce 3+ . The garnet oxynitride phosphor exhibit excellent thermal stability with high quantum efficiency and is a promising candidate for warm white LED.